Kinetics and kinematics of dog walk exercise in agility dogs of different experiences - Godoy, Roberta Ferro de (2023)
The injury rate in agility dogs is relatively high compared to the general population. No study to date has considered the biomechanical effects of the dog walk obstacle in agility trials, highlighting a research need. The aim of this study was to assess forelimb joint kinematics and peak ground reaction forces (PVF) over a dog walk agility obstacle and correlate with experience. Dogs were filmed running across a Kennel Club (KC) standard dog walk for kinematics analysis. Two pressure sensors were secured to the (1)  dog walk contact area at exit and (2) ground at the end of the dog walk  (landing area) for kinetics analysis. Forelimb joints angles and  PVF at the contact zone at the walk exit and landing  were analysed. A key finding is that the way a dog will move across the obstacle changes depending on their level of experience, with experienced dogs showing faster obstacle negotiation and increased flexion of the elbow joint compared to inexperienced competitors. Higher speeds over the dog walk also resulted in significantly increased elbow joint flexion. Another important finding is that PVF at landing are higher is dogs  that are faster and also in dogs performing running technique in comparison to  stopped technique,. Overall, dog walk obstacle created more forelimbs joint flexion and similar PVF in comparison with previously studied agility contact obstacles which leads us to conclude that further research is required to ascertain the long term health implications for dogs used in agility trials.